Incidence and Characteristics of Psychological Trauma in Alcohol and Substance Abuse Disorder - Çetin Şeker, Burcu; Dinç, Mehmet; Işık, Sultan; Ögel, Kültegin (Addicta: The Turkish Journal on Addictions, 2019)
There are many researches show the relationship between addiction and trauma. Increasing the number of these researches indicates the importance of this issue. In company with existing researches, our purpose in this research was to analyze traumatic events and its effects on addiction among individuals who applied an outpatient addiction service. This research carried out on 322 individuals who applied Green Crescent Counseling Center (YEDAM) for addiction treatment. Various scales are used in this study for measuring the severity and characteristics of addiction, family characteristics, and the characteristics of traumatic events. These scales are the BAPİ (Bağımlılık Profil İndeksi [Addiction Profile Index]), BAPİ-K (BAPİ Clinical Form, BAPİ-A (BAPİ Family Assessment Form) and the Kocaeli Short Screening Scale for Psychological Trauma (Kocaeli-SHORT). 97.5% of the applicants have been exposed at least one traumatic event and 21.7% of those applicants met the Post Traumatic Stress Disorder (PTSD) risk criteria. Demographic features show that, PTSD risk group has higher average point of economic difficulties which an individual cannot afford even their basic needs than others. Characteristics of addiction of PTSD risk group indicates that, PTSD risk group has higher average points on the severity of addiction, substance-use features, effects of substances on their lives and severity of craving than others. Besides, PTSD risk group also has higher average points on depression, anxiety, impulsivity and lack of assertiveness. There is no significance on family relationship between PSTD risk group and others. Result: It has been analyzing the relationship between addiction and trauma with acquired data in this research. According to the results of this research, we emphasize that traumatic events and PTSD risk have effects on addiction and its severity. Besides, it is necessary to focus on trauma symptoms while treating addiction. To